Dynamic transitions in RNA polymerase II density profiles during transcription termination - Grosso, Ana Rita (2022)
Eukaryotic protein-coding genes are transcribed by RNA polymerase II (RNAPII) through a cycle composed of three main phases: initiation, elongation, and termination. Recent studies using chromatin immunoprecipitation coupled to high-throughput sequencing suggest that the density of RNAPII molecules is higher at the 3′-end relative to the gene body. Here we show that this view is biased due to averaging density profiles for "metagene" analysis. Indeed, the majority of genes exhibit little, if any, detectable accumulation of polymerases during transcription termination. Compared with genes with no enrichment, genes that accumulate RNAPII at the 3′-end are shorter, more frequently contain the canonical polyadenylation [poly(A)] signal AATAAA and G-rich motifs in the downstream sequence element, and have higher levels of expression. In 1% to 4% of actively transcribing genes, the RNAPII enriched at the 3′-end is phosphorylated on Ser5, and we provide evidence suggesting that these genes have their promoter and terminator regions juxtaposed. We also found a striking correlation between RNAPII accumulation and nucleosome organization, suggesting that the presence of nucleosomes after the poly(A) site induces pausing of polymerases, leading to their accumulation. Yet we further observe that nucleosome occupancy at the 3′-end of genes is dynamic and correlates with RNAPII density. Taken together, our results provide novel insight to transcription termination, a fundamental process that remains one of the least understood stages of the transcription cycle.